Bis-nor-diterpene from Cnidoscolus quercifolius (Euphorbiaceae) induces tubulin depolymerization-mediated apoptosis in BRAF-mutated melanoma cells. (1st March 2022) - de Oliveira-Júnior, Raimundo Gonçalves; Alves Ferraz, Christiane Adrielly; de Oliveira, Ana Paula; da Cruz Araújo, Edigênia Cavalcante; Prunier, Grégoire; Beaugeard, Laureen; Groult, Hugo; Picot, Laurent; de Alencar Filho, Edilson Beserra; El Aouad, Noureddine; Rolim, Larissa Araújo; Almeida, Jackson Roberto Guedes da Silva
Abstract: A phytochemical investigation of cytotoxic extract and fractions of Cnidoscolus quercifolius Pohl led to isolation of five terpenoids, including three lupane-type triterpenes (1–3 ) and two bis- nor -diterpenes (4–5 ). Compounds 4 (phyllacanthone) and 5 (favelanone) are commonly found in this species and have unique chemical structure. Although their cytotoxic activity against cancer cells has been previously reported, the anticancer potential of these molecules remains poorly explored. In this paper, the antimelanoma potential of phyllacanthone (PHY) was described for the first time. Cell viability assay showed a promising cytotoxic activity (IC50 = 40.9 μM) against chemoresistant human melanoma cells expressing the BRAF oncogenic mutation (A2058 cell line). After 72 h of treatment, PHY inhibited cell migration and induced apoptosis and cell cycle arrest ( p < 0.05). Immunofluorescence assay showed that the pro-apoptotic effect of PHY is probably associated with tubulin depolymerization, resulting in cytoskeleton disruption of melanoma cells. Molecular docking investigation confirmed this hypothesis given that satisfactory interaction between PHY and tubulin was observed, particularly at the colchicine binding site. These results suggest PHY from C. quercifolius could be potential leader for the design of new antimelanoma drugs. Graphical abstract: Image 1 Highlights: Bioguided purification led to the isolation of phyllacanthone (PHY) from C. quercifolius. PHY inhibited cell proliferation and migration, and induced apoptosis and cell cycle arrest. Pro-apoptotic effect of PHY was associated with tubulin depolymerization. New PHY-structure based molecules could be designed to obtain antimelanoma drug candidates.